The shared sovereignty of the 1876 constitution in comparison to the national sovereignty of the 1812 constitution - López Sánchez, Carmina (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2015)
The Constitution of 1812 marked the beginning of Spain’s constitutional history and became a symbol of liberalism. The development of its ideas took place intermittently throughout the 19th Century until branching off into a constitutional model, as envisaged by Cánovas del Castillo. The basis for this was the so-called “internal constitution” which implied a sovereignty shared between the Parliament or “Cortes” and the King.